Thermal degradation of epoxidized natural rubber in presence of neodymium stearate - 罗勇悦 杨昌金 陈帮乾 许逵 钟杰平 彭政 吕臻 王庆煌 (Journal of rare earths, 2013)
The effect of neodymium stearate （NdSt） synthesized by saponification method on thermal degradation and thermo-oxidative degradation of expoxidized natural rubber with 25 mol.% epoxidation （ENR25） was investigated by thermogravimetric analysis （TGA）, and the structure of ENR25 vulcanized with NdSt after thermo-oxidative decomposition was characterized using Fourier transform infared spectroscopy-attenuated total-reflectance （FTIR-ATR）. The thermal degradation kinetic parameters of ENR25 with different loadings of NdSt were determined by Coats-Redfern method. The results showed that the thermal degradation of ENR25 in nitrogen was a one-step reaction regardless of NdSt content, whereas the thermo-oxidative degradation was a multiple-step reaction. The thermal and thermo-oxidative stability of the ENR25 vulcanizates with the addition of NdSt was higher than that of pure ENR25 vulcanizates. The ENR25 vulcanizates with the incorporation of 1 phr （per hundred parts of rubber） NdSt imparted the highest activa- tion energy （E） of thermal and thermo-oxidative degradation. This could be attributed to the many unoccupied orbits in rare earth Nd, which could capture the free radicals and make the epoxide groups stable in the process of thermal and thermo-oxidative degradation for ENR25.